FAKTOR-FAKTOR YANG MEMPENGARUHIKUALITAS LABA (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSAEFEKINDONESIA PADA PERIODE 2014-2016) - Susanti Purboningsih, 14.05.52.0106; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2018)
This study aims to examines and analyzes the effect of capital structure, company size, profit growth, liquidity, profitability and liquidity to the quality of earnings at manufacturing companies listed on the Stock Exchange 2014-2016. In this study the researchers used the financial population data of manufacturing companies listed on the Stock Exchange during the years 2014-2016. The relationship between variables and or described by using multiple regression analysis. The result showed that the variables of capital structure, earnings growth, and liquidity is not significant positive effect on the quality of eranings. In the variable size of the company and significant positive effect on the quality of earnings. While the profitability variable and no significant negative effect on the quality of earnings. Keywords : Capital Structure, Company Size, Income Gwowth, Liquidity, Profitability, and Quality of Earnings.